Study of Community Knowledge on the Impact of Waste Burning on Air Pollution in Cikopomayak Village, Jasinga District, Bogor Regency - Winarno Winarno; Maulana Andiansyah; Indah Meitasari; Alwin Alwin (STKIP Taman Siswa Bima, 2024)
Irregular waste management in Indonesia occurs because most of the waste generated does not undergo a good management process, resulting in environmental problems or problems. This happens in Cikopomayak Village, where the community in processing waste uses the burning method with the aim of reducing the amount of waste that causes air pollution. The purpose of this study was to determine the extent of community knowledge about the impact of burning waste and community behavior in waste management. The method used in the research is descriptive method, qualitative approach. By using data collection techniques in the form of survey techniques, observation, documentation and data analysis. The instrument used in this study was a questionnaire. The research location was conducted in Cikopomayak Village, Jasinga District, Bogor Regency, the research was conducted from February to April 2024. The research sample obtained was 78 respondents from 356 heads of families who were calculated using the Slovin formula. The results of the study showed that the knowledge of the Cikopomayak Village community fell into the poor category, which was 54% higher than the community who had a good level of knowledge, which was 46% and the Cikopomayak Village community also had poor waste management behavior, which was 62% much higher than the community who had good waste management behavior, which was 38%. Poor knowledge and behavior are influenced by the low level of public awareness and understanding of the environment.